The Influence of Knowledge Manegement on Employe Performance With Work-Life Balance as A Moderating Variable - Nancy Kaligis, Jenny (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Researchers believe that the Management Knowledge variable can have a positive relationship and a significant influence on employee performance because the resulting activities can be structured and systematic so that targets achieved can be achieved easily and ultimately this can improve employee performance. Therefore, this research aims to analyze the influence of knowledge management on employee performance. In contrast to previous research, this research adds the Work-Life Balance variable as a moderating variable due to external factors from Knowledge Management which produce planned, systematic and structured activities if supported by a balanced lifestyle of employees which is believed to be able to further improve employee performance. This research is quantitative research with an explanatory approach. The data used in this research is primary data that researchers obtained from the method of distributing questionnaires to 300 Bank BTN Syari'ah employees spread throughout Indonesia. These data were analyzed using the Samrt PLS 4.0 tool analysis. The result in this research show the influence of the Knowledge Management variable which is positive and significant on employee performance because the P-Values value has a value less than the significance level of 0.05, namely 0.005. Apart from that, the Work-Life Balance variable is able to moderate the influence of the Knowledge Management variable on employee performance because the P-Values value of 0.000 is below the significance level of 0.05. Thus, the first and second hypotheses in this research can be accepted.